PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA MELALUI PRESTASI KERJA GURU PADA SDN SE-GUGUS 3 BALIKPAPAN KOTA - jurnalpps pps; Isti Warsini; Nugroho Mardi Wibowo; C. Sri Hartati (Jurnal Manajerial Bisnis, 2018)
This study aims to describe, knowing the simultaneous and partial effect of compensation, work motivation, work performance and teacher job satisfaction on SDN in Cluster 3 Balikpapan City through work performance. This study uses a quantitative approach and type of explanatory research. The population in this study were all teachers of SDN in Cluster 3 Balikpapan City. The sample of this study amounted to 55 teachers. The sampling technique uses saturated samples. Data collection methods use questionnaires and documentation. Data analysis method used descriptive analysis and path analysis. The results of the study showed that compensation had a significant effect on the work performance of teachers at SDN in Cluster 3 Balikpapan City. Work motivation has a significant effect on teacher work performance. Compensation has a significant effect on teacher job satisfaction. Work motivation has a significant effect on teacher job satisfaction. Work performance has a significant effect on teacher job satisfaction. Compensation has a significant effect on teacher job satisfaction at SDN in Balikpapan City 3 through work performance. Work motivation has a significant effect on teacher job satisfaction at SDN in Cluster 3 Balikpapan City through work performance. Keywords: compensation, work motivation, job satisfaction, work performance